Regulation of mating type switching by the mating type genes and RME1 in Ogataea polymorpha. Issue 1 (December 2017) - Yamamoto, Katsuyoshi; Tran, Thi; Takegawa, Kaoru; Kaneko, Yoshinobu; Maekawa, Hiromi
Abstract Saccharomyces cerevisiae and its closely related yeasts undergo mating type switching by replacing DNA sequences at the active mating type locus (MAT ) with one of two silent mating type cassettes. Recently, a novel mode of mating type switching was reported in methylotrophic yeast, includingOgataea polymorpha, which utilizes chromosomal recombination between inverted-repeat sequences flanking twoMAT loci. The inversion is highly regulated and occurs only when two requirements are met: haploidy and nutritional starvation. However, links between this information and the mechanism associated with mating type switching are not understood. Here we investigated the roles of transcription factors involved in yeast sexual development, such as mating type genes and the conserved zinc finger protein Rme1. We found that co-presence of mating typea 1 andα 2 genes was sufficient to prevent mating type switching, suggesting that ploidy information resides solely in the mating type locus. Additionally, RME1 deletion resulted in a reduced rate of switching, and ectopic expression ofO. polymorpha RME1 overrode the requirement for starvation to induceMAT inversion. These results suggested that mating type switching inO. polymorpha is likely regulated by two distinct transcriptional programs that are linked to the ploidy and transmission of the starvation signal.